Attributive portrait of human’s internal qualities in Russian and Chinese linguistic culture - Irina M. Subbotina, Yulia A.cv, Svetlana V. Funikova, Lyudmila F. Svoykina, (Opción, 2019)
The article is devoted to the problem of studying the attributive portrait of human’s internal qualities in Russian and Chinese linguistic culture via analysis of language material; comparison; methods of classification, generalization, and differentiation. As a result, when a person is calm, fluid, flexible in his actions, it indicates his sensitivity and therefore impartiality. In conclusion, in Russian linguacultural there are more units with a positive assessment of the individual. According to the attributive model of the Chinese language, the character of a person is more pronounced with positive adjectives.